Comparison of microwave and heat treatment extraction methods and microbiological stability analysis of a functional drink from Perilla frutescens - Nhat Anh Duong; Nguyen Tri Yen Chi (Applied Food Research, 2025)
Perilla frutescens (L.) Britton and Chrysanthemum indicum L. are well-known for their high content of bioactive compounds with significant antioxidant properties. This study investigates the effects of various extraction and thermal treatment conditions on the biological activity and sensory properties of a perilla-based beverage supplemented with C. indicum. The impact of microwave-assisted extraction (MAE) and heat treatment on polyphenols, reducing sugars, anthocyanins, and flavonoids was analyzed to determine optimal extraction conditions. Additionally, the sensory attributes of the beverage were assessed through a panel evaluation to establish an optimal formulation incorporating C. indicum extract and steviol glycosides. The results indicate that an 8-minute heat extraction at 95 °C - 100 °C optimally retains biologically active compounds (concentrations of polyphenols, reducing sugars, and anthocyanins). Sensory evaluations revealed that adding 2 % C. indicum extract and 3.32 % steviol glycosides resulted in the highest acceptability. Thermal treatment studies demonstrated that pasteurization at 80 °C for 10 min minimized bioactive compound degradation while ensuring microbial stability. These findings provide valuable insights into optimizing processing conditions for functional beverages rich in natural antioxidants.